Paroxysmal Autonomic Instability with Dystonia (PAID) Syndrome: A Rare Occurrence - Vayara Perumall Vinodh; Sivakumaran Rajandran; Rajesh Kumar Muniandy; Pulivendhan Sellamuthu (Gazi Medical Journal)
Paroxysmal autonomic instability with dystonia (PAID) is still under-recognized in clinical settings due to its rarity. This syndrome may mimic certain life-threatening conditions. We present a rare case of PAID syndrome. A 45-year-old female was brought to the hospital with an altered level of consciousness. An urgent computed tomography of the brain was performed, and a diagnosis of obstructive hydrocephalus secondary to cerebellar hemorrhage was made. Her family refused major surgery but consented to cerebrospinal fluid diversion. However, after several days in the ward, she developed ventriculitis. She was successfully treated with intravenous ceftriaxone. After several weeks at home, she developed episodic attacks of hypertension, tachycardia, and diaphoresis with hyperthermia and diaphoresis. She also had episodes of restlessness and generalized dystonic movements. She was diagnosed with PAID syndrome, and treatment was initiated. Her symptoms were successfully treated after three days.